Performance Analysis of Vapor Compression Heat Pump Dryer for Zedoary Drying (Curcuma zedoaria (Berg.) Roscoe) - Hayatri Sali Setia; Leopold Oscar Nelwan; I Wayan Astika; Rokhani Hasbullah (Jurnal Keteknikan Pertanian, 2022)
Zedoary (Curcuma zedoaria (Berg.) Roscoe) drying in simplicia form requires a proper treatment because the moisture content is high about 80–90 % that have perishable properties. Temperature, relative humidity and air flow rate are influential factors in drying medicinal plants then proper drying conditions need to be known. Dryer with vapor compression heat pump (VCHP) system is one of mechanical dryers as an alternative drying method to shorten drying time and maintain the quality. In this system, the environmental air flow is passed through the evaporator and condenser. The configuration of air flow passing through these two components is assessed in proportion to increase its effect on drying air conditions. The study aims to find the best configuration of air flow rate from VCHP which produces drying air conditions that are suitable for zedoary drying then analyze the performance of VCHP. The research was conducted by configuring the air flow and analyzing dryer performance of VCHP system. The results obtained the best configuration of air flow for zedoary drying are: (i) the air inlet before evaporator is given an inhibitor, (ii) the air inlet before condenser is closed. This configuration provides the highest sensible heating effect and the highest decrease in drying air humidity. VCHP performance test results for zedoary drying are: (i) COPhp is 3.11, (ii) STEC value is 4.066 MJ/kg, (iii) SMERT value is 0.870 kg/kWh, and (iv) SMERTot value is 0.449 kg/kWh. The STEC, SMERT and SMERTot values obtained are affected by drying time.